Efficacy of green urea for sustainable agriculture - Yahya, N. (Springer Verlag, 2018)
Fertilizer is an essential crop yielding factor in all agricultural production systems. Adaptation of latest fertilizer technology and efficient management practice plays vital role to ensure sustainable quantity and quality of crop yield. At the same time, environmental blueprints such as leaching, volatilization, and groundwater pollution could also be reduced. The need of eco-friendly fertilizer and the aim for this solution by providing a green technology in ammonia and urea production via electromagnetic and nanotechnology has been well described in the previous chapters. In order to add value on the Green Urea, the studies on its efficiency of application through slow release properties and nano-based coating technology is conducted and described in this chapter. Green Urea coated with organic material, chitosan showed better effectiveness in dissolution test compared to zeolite and carbon structure materials. Nursery and field studies indicate that oil palm and spinach treated with Green Urea has better vegetative growth compared to conventional urea. This information could serve as an insight for larger scale applications in field trials. In another point of view, the efficacy of Green Ureaâs delivery ability in agriculture production system can be further enhanced by integrating vertical farming and elements of digital technology. Combination of these proposed ideas would place the technology of Green Urea, and its application in agriculture to be in line with Fourth Industrial Revolution. Therefore, this would definitely make a great impact to the economic and sustainability challenges that are currently being highlighted now. Â© 2018, Springer Nature Singapore Pte Ltd.